2014
DOI: 10.2214/ajr.13.11337
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Energy Liver CT: Effect of Monochromatic Imaging on Lesion Detection, Conspicuity, and Contrast-to-Noise Ratio of Hypervascular Lesions on Late Arterial Phase

Abstract: Viewing dual-energy CT images may result in the greatest subjective lesion conspicuity and measured contrast-to-noise ratio at 50 keV with equal detection of hyperenhancing liver lesions compared with viewing 77-keV images alone. In addition, the radiation doses of dual-energy CT may be similar to those of single-energy CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(62 citation statements)
references
References 17 publications
4
58
0
Order By: Relevance
“…Schuman et al evaluated single-source DE-VM images in 72 patients with 128 lesions and compared visual evaluation of 77 keV images with DE-VM images from 40 to 77 keV. They found that CNR and subjective conspicuity were greater at 50 keV [11]. Our data confirm the previous findings, but add to this knowledge base by including patients with a dose-matched SE-LTP acquisition to the analysis.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Schuman et al evaluated single-source DE-VM images in 72 patients with 128 lesions and compared visual evaluation of 77 keV images with DE-VM images from 40 to 77 keV. They found that CNR and subjective conspicuity were greater at 50 keV [11]. Our data confirm the previous findings, but add to this knowledge base by including patients with a dose-matched SE-LTP acquisition to the analysis.…”
Section: Discussionsupporting
confidence: 83%
“…Several studies have investigated the use of DE VM imaging on both anthropomorphic phantoms with simulated abdominal lesions, as well as in patient cohorts [711]. …”
mentioning
confidence: 99%
“…It has been shown that an optimal keV exists that has the highest contrast to noise ratio (CNR) [10]. Reports have also demonstrated that the selection of keV could influence lesion conspicuity [11]. We hypothesize that VMIs acquired on a PCD-CT scanner with a fixed tube potential and created at a fixed keV can provide comparable or improved iodine CNR to SE CT with optimized kV and DSDE with optimized tube potential pairs across different patient sizes.…”
Section: Background and Purposementioning
confidence: 99%
“…One of DECT’s major strengths is improving visualization of contrast enhancement, potentially increasing the visibility of such entities as hypervascular liver lesions, [1] hypodense and hyperdense pancreatic tumors [24], and pulmonary emboli [5,6]. Early work shows dual energy CT also has the ability to provide information that would have required separate pre-and postcontrast imaging, offering opportunities for decreasing radiation dose [7], as well as providing unique information that is being increasingly utilized to characterize materials, for example the management of gout [8], and the removal of calcified plaque to improve the accuracy of CT angiography for such purposes as the assessment of vascular stenoses [9].…”
Section: Introductionmentioning
confidence: 99%